Sie sind auf Seite 1von 12

RECURRENCE OF J(x)

RECURRENCE FORMULAE:
𝑑
1. 𝑥 𝑛 𝐽𝑛 𝑥 = 𝑥 𝑛 𝐽𝑛−1 𝑥
𝑑𝑥
𝑑
2. [𝑥 −𝑛 𝐽𝑛 𝑥 ] = −𝑥 −𝑛 𝐽𝑛+1 (𝑥)
𝑑𝑥
n
3. 𝐽𝑛 𝑥 + 𝐽𝑛′ 𝑥 = 𝐽𝑛−1 (𝑥)
x
𝑛
4. 𝐽 𝑛 𝑥 − 𝐽 ′𝑛 𝑥 = 𝐽 𝑛+1 𝑥
𝑥
′ 1
5. 𝐽 𝑛 𝑥 = [ 𝐽 𝑛−1 𝑥 − 𝐽 𝑛+1 𝑥
2
]
𝑥
6. 𝐽𝑛 𝑥 =
2𝑛
[𝐽 𝑛−1 𝑥 + 𝐽 𝑛+1 𝑥 ]
𝒅
𝒙𝒏 𝑱𝒏 𝒙 = 𝒙𝒏 𝑱𝒏−𝟏 𝒙
𝒅𝒙

∞ 𝑥 2 𝑟+𝑛
𝐽𝑛 𝑥 = ෍ −1 2
𝑟! Γ(𝑛 + 𝑟 + 1)
𝑟=0

∞ 2 𝑟+2𝑛
𝑥
𝑥 𝑛 𝐽 𝑛 𝑥 = ෍ −1 𝑟
𝑟! 22𝑟+𝑛 Γ(𝑛 + 𝑟 + 1)
𝑟=0


𝑑 𝑛 2 𝑟 + 𝑛 𝑥 2 𝑟+𝑛 −1
𝑟
[𝑥 𝐽 𝑛 𝑥 ] = ෍ −1
𝑑𝑥 𝑟! 22𝑟+𝑛 Γ(𝑛 + 𝑟 + 1)
𝑟=0

∞ 2𝑟+𝑛 −1
2 𝑟 + 𝑛 𝑥
= 𝑥 𝑛 ෍ −1 𝑟
𝑟! 22𝑟+𝑛 𝑛 + 𝑟 Γ(𝑛 + 𝑟 + 1 − 1)
𝑟=0
∞ 𝑥 2 𝑟+𝑛−1
= 𝑥 𝑛 ෍ (−1)𝑟 2
𝑟! Γ(𝑛 − 1 + 𝑟 + 1)
𝑟=0
=𝑥 𝑛 𝐽 𝑛−1 (𝑥) (Proved)

𝒅
 𝒙−𝒏 𝑱𝒏 𝒙 = −𝒙−𝒏 𝑱𝒏+𝟏 𝒙
𝒅𝒙 ∞ 𝑥
(2)2𝑟+𝑛
𝑟
𝐽𝑛 𝑥 = ෍ −1
𝑟! Γ(𝑛 + 𝑟 + 1)
𝑟=0


𝑥 2𝑟
𝑥 −𝑛 𝐽𝑛 𝑥 = ෍ −1 𝑟 2𝑟+𝑛
2 𝑟! Γ(𝑛 + 𝑟 + 1)
𝑟=0


𝑥 2𝑟
𝑥 −𝑛 𝐽𝑛 𝑥 = ෍ −1 𝑟
22𝑟+𝑛 𝑟! Γ(𝑛 + 𝑟 + 1)
𝑟=0


2𝑟−1
𝑑 2𝑟 𝑥
[𝑥 −𝑛 𝐽𝑛 𝑥 ] = ෍ −1 𝑟 2𝑟+𝑛
𝑑𝑥 2 𝑟! Γ(𝑛 + 𝑟 + 1)
𝑟=0
r= k+1 r= 0 ; k= -1 r = ∞ ; k= ∞

𝑘+1
2 𝑘 + 1 𝑥 2 𝑘+1 −1
= ෍ −1
22 𝑘+1 +𝑛 (𝑘 + 1 )! Γ(𝑛 + 𝑘 + 1 + 1)
𝑘=−1

∞ 2𝑘+1+ 𝑛 (𝑘 + 1)
(𝑥/2)
= 𝑥 −𝑛 ෍ −1 𝑘+1
Γ 𝑛 + 𝑘 + 1 + 1 . (𝑛 + 𝑘 + 1)!
𝑘=0

∞ 2𝑘+1+ 𝑛 (𝑘 + 1)
(𝑥/2)
= − 𝑥 −𝑛 ෍ −1 𝑘
Γ 𝑛 + 𝑘 + 1 + 1 . 𝑘 + 1 . 𝑘!
𝑘=0

= −𝑥 −𝑛 𝐽 𝑛+1 (𝑥)
(Proved)
𝑥
 𝐽𝑛 𝑥 = 𝐽 𝑛−1 𝑥 + 𝐽 𝑛+1 𝑥
2𝑛

𝑑
From 𝑥 𝑛 𝐽𝑛 𝑥 = 𝑥 𝑛 𝐽𝑛−1 𝑥
𝑑𝑥
𝑥 𝑛 𝐽𝑛′ 𝑥 + 𝐽𝑛 𝑥 𝑛 𝑥 𝑛−1 = 𝑥 𝑛 𝐽𝑛−1 (𝑥) ÷ 𝑥𝑛
𝑛
𝐽𝑛′ 𝑥 + 𝐽𝑛 𝑥 = 𝐽𝑛−1 (𝑥) (1.)
𝑥

𝑑
From [𝑥 −𝑛 𝐽𝑛 𝑥 ] = −𝑥 −𝑛 𝐽𝑛+1 (𝑥)
𝑑𝑥
𝑥 −𝑛 𝐽𝑛′ 𝑥 + 𝐽𝑛 𝑥 −𝑛 𝑥 −𝑛−1 = −𝑥 −𝑛 𝐽𝑛+1 (𝑥) ÷ 𝑥𝑛
′ −𝑛
𝐽𝑛 𝑥 + 𝐽𝑛 𝑥 = − 𝐽𝑛+1 (𝑥) (2.)
𝑥

(1.) – (2.)
2𝑛
𝐽𝑛 𝑥 = 𝐽𝑛−1 𝑥 + 𝐽 𝑛+1 𝑥
𝑥
𝑥
𝐽𝑛 𝑥 = [ 𝐽𝑛−1 𝑥 − 𝐽 𝑛+1 𝑥 ]
2𝑛
(Proved)
′ 1
 𝐽 𝑛 𝑥 = [ 𝐽 𝑛−1 𝑥 − 𝐽 𝑛+1 𝑥 ]
2

From (1) and (2)


𝑛
𝐽 𝑛−1 𝑥 = 𝐽 ′𝑛 𝑥 + 𝐽𝑛 𝑥 (1.)
𝑥
′ 𝑛
− 𝐽 𝑛+1 𝑥 = 𝐽 𝑛 𝑥 − 𝐽𝑛 𝑥 (2.)
𝑥
(1.) + (2.)
2 𝐽 ′𝑛 𝑥 = 𝐽 𝑛−1 𝑥 − 𝐽 𝑛+1 𝑥

′ 1
𝐽 𝑛 𝑥 = [ 𝐽 𝑛−1 𝑥 − 𝐽 𝑛+1 𝑥 ]
2
(Proved)
𝑛
 𝐽 𝑛 𝑥 − 𝐽 ′𝑛 𝑥 = 𝐽 𝑛+1 𝑥
𝑥

′ 𝑛
𝐽 𝑛 𝑥 = 𝐽 𝑛 𝑥 − 𝐽 𝑛+1 𝑥
𝑥

From (2)
𝑛
−𝐽𝑛+1 𝑥 = 𝐽 ′𝑛 𝑥 − 𝐽𝑛 𝑥
𝑥

𝑛
𝐽 ′𝑛 𝑥 = 𝐽𝑛 𝑥 − 𝐽𝑛+1 (𝑥) (Proved)
𝑥

𝑥
 𝐽𝑛 𝑥 = [ 𝐽 𝑛−1 𝑥 + 𝐽 𝑛+1 𝑥 ]
2𝑛

2𝑛
𝐽𝑛+1 𝑥 = 𝐽𝑛 𝑥 − 𝐽𝑛−1 (𝑥)
𝑥
From (3) formula,
𝑥
𝐽𝑛 𝑥 = [ 𝐽𝑛−1 𝑥 + 𝐽𝑛+1 𝑥 ]
2𝑛
2𝑛
𝐽𝑛+1 𝑥 = 𝐽 𝑥 − 𝐽𝑛−1 (𝑥) (Proved)
𝑥 𝑛

Problems:
STATEMENT: Express 𝐽5 in terms of 𝐽0 and 𝐽1

2𝑛
𝐽𝑛+1 𝑥 = 𝐽𝑛 𝑥 − 𝐽𝑛−1 𝑥
𝑥
8
n= 4, 𝐽5 𝑥 = 𝐽4 𝑥 − 𝐽3 𝑥
𝑥
n= 3,
6
𝐽4 𝑥 = 𝐽3 𝑥 − 𝐽2 𝑥
𝑥

n= 2,

4
𝐽3 𝑥 = 𝐽2 𝑥 − 𝐽1 𝑥
𝑥
n= 1,

2
𝐽2 𝑥 = 𝐽1 𝑥 − 𝐽0 𝑥
𝑥
8 6
𝐽5 𝑥 = 𝐽3 𝑥 − 𝐽2 𝑥 − 𝐽3 𝑥
𝑥 𝑥

48 8
= 2 𝐽3 𝑥 − 𝐽2 𝑥 − 𝐽3 𝑥
𝑥 𝑥

48 8
= 2 − 1 𝐽3 𝑥 − 𝐽2 𝑥
𝑥 𝑥

48 4 8
= 2 −1 𝐽2 𝑥 − 𝐽1 𝑥 − 𝐽2 𝑥
𝑥 𝑥 𝑥

192 4 48 8
= 3
− 𝐽2 𝑥 − 2 − 1 𝐽1 𝑥 − 𝐽2 𝑥
𝑥 𝑥 𝑥 𝑥
192 12 48
= 3
− 𝐽2 𝑥 − 2 − 1 𝐽1 𝑥
𝑥 𝑥 𝑥

192 12 2 48
= 3
− 𝐽1 𝑥 − 𝐽0 𝑥 − 2 − 1 𝐽1 𝑥
𝑥 𝑥 𝑥 𝑥

384 24 48 192 12
= 4
− 2 − 2 + 1 𝐽1 𝑥 − 3
− 𝐽0 𝑥
𝑥 𝑥 𝑥 𝑥 𝑥

384 72 192 12
𝐽5 = 4
− 2 + 1 𝐽1 𝑥 − 3
− 𝐽0 𝑥
𝑥 𝑥 𝑥 𝑥